Legal education in Peru: Are we ready for integration and globalization? - Mac Lean, Ana Cecilia (2015)
DURING the sixties, higher education was mainly given by public universities. There were twenty-one public and ten private universities. 1 Growth in education went from 2.3 percent in 1961 to 4.4 percent in 1972, and jumped to 9.9 percent in 1981.